Control of active nematics - Thijssen, K (2021)
Active matter describes systems, such as bacterial suspensions, cellular tissue or cytoskeleton biopolymers, that extract energy from their surroundings at the single-particle level and convert it into mechanical work. The resulting active work can be manifested in the form of self-propulsion and stress generation. The continuous injection of energy or activity may lead to complex, collective flow patterns and, for active materials composed of particles with nematic-like symmetry, this can produce orientational order and topological defects in the orientation field. These materials are commonly described as active nematics. An important theme in active nematic research is active turbulence, a steady-state in which hydrodynamic instabilities result in chaotic collective flows.